S126. EMOTION-SPECIFIC PERFORMANCE ON EMPATHY TASKS IN SCHIZOPHRENIA: INFLUENCE OF METACOGNITIVE CAPACITY. (9th April 2019) - Bonfils, Kelsey; Haas, Gretchen; Salyers, Michelle; Lysaker, Paul
Abstract: Background: Numerous studies suggest that people with schizophrenia have problems in social relationships. Laboratory-based approaches to investigating these problems often examine emotion recognition and reveal more accurate detection of positive emotions (e.g., happiness) in contrast to negative emotions (e.g., fear). These findings have held in both facial and prosodic emotion recognition tasks. Here, we examine whether similar patterns of detection exist in an empathy task with 6 emotion conditions. Second, we examine the relationship between metacognitive capacity (i.e., ability to think about cognitive experiences) and recognition of those 6 emotions. We propose that metacognitive awareness of others' thoughts and emotions will more greatly influence emotion recognition than metacognitive awareness of one's own thoughts and emotions (i.e., self-reflectivity). Methods: 58 people with schizophrenia or schizoaffective disorder completed a computerized, performance-based measure of empathy with three tasks: emotion recognition (ER), emotional perspective-taking (EPT), and affective responsiveness (AR). All tasks presented stimuli in 6 emotion conditions: happiness, neutral, sadness, anger, fear, and disgust. Participants' metacognitive capacities were evaluated with the Metacognition Assessment Scale-Abbreviated (MAS-A). The MAS-A produces a total score and subscores for four domains: Self-Reflectivity, Awareness of the Other, Decentration, and Mastery. Analyses included within-subjects ANOVAs and correlations. Results: Emotion-specific performance significantly varied within each task (ER: F[4.00, 14.27] = 14.68, p<.001; EPT: F[4.29, 4952.42] = 17.14, p<.001; AR: F[3.68, 309.74] = 24.29, p<.001). The pattern of emotion-specific performance was similar across tasks, with accuracy for happiness significantly better than for all other emotions. On two out of three tasks, participants were least accurate in detecting anger. Across tasks, participants performed best on ER, followed by AR, and worst on EPT (F[2, 1332.93] = 20.37, p<.001). MAS-A Self-Reflectivity was positively associated with accuracy for each emotion and on each task. MAS-A Awareness of the Other was associated with total EPT and AR (but not ER), as well as the emotions disgust, fear, and sadness (but not happiness or neutral). Discussion: Taken together, results suggest across empathy tasks that people with schizophrenia are more accurate in detecting positive emotions and less accurate in detecting negative, especially anger. Clinically, this suggests that targeting detection of negative emotions in social cognitive or social skill treatments could optimize outcomes. Findings also highlight that emotion recognition in schizophrenia, a more basic skill, may be most dependent upon one's metacognitive understanding of one's own thoughts and emotions, while more complex social cognitive processes, such as emotional perspective-taking, require greater metacognitive awareness of the other.